The 8th International Conference on Software, Knowledge, Information Management and Applications (SKIMA 2014) 2014
DOI: 10.1109/skima.2014.7083561
|View full text |Cite
|
Sign up to set email alerts
|

An efficient abnormal beat detection scheme from ECG signals using neural network and ensemble classifiers

Abstract: This paper presents an investigation into the development of an efficient scheme to detect abnormal beat from lead II Electro Cardio Gram (ECG) signals. Firstly, a fast ECG feature extraction algorithm was proposed which could extract the locations, amplitudes waves and interval from lead II ECG signal. We then created 11 customized features based on the outputs of the feature extraction algorithm. Then, we used these 11 features to train an artificial neural network and an ensemble classifier respectively for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Rules are derived based on the ST-segment value depending on the time between the R-peak and the start of the ST-segment slope. In Reference [51], the authors have used an ensemble learning technique called Adaptive Boosting (AdaBoost) also known as meta-learning, used to enhance binary classification efficiency in detecting abnormal beats from the ECG signal and have evaluated on three databases of MITDB, QT [52], and ESCDB. Studies have shown that Artificial Neural Networks (ANN) are powerful data analysis tools.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…Rules are derived based on the ST-segment value depending on the time between the R-peak and the start of the ST-segment slope. In Reference [51], the authors have used an ensemble learning technique called Adaptive Boosting (AdaBoost) also known as meta-learning, used to enhance binary classification efficiency in detecting abnormal beats from the ECG signal and have evaluated on three databases of MITDB, QT [52], and ESCDB. Studies have shown that Artificial Neural Networks (ANN) are powerful data analysis tools.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…Ahmed et al categorized the features for classification in time-, frequency-, and time-frequency-based features [19]. In the literature, the variety of classifiers ranges from neural networks [27] to k-nearest neighbors [28]. In 2021, Hua et al developed an approach for information divergences based on divergence-based matrix information geometry detectors [29].…”
Section: Introductionmentioning
confidence: 99%
“…The constructed features convey a subset of medically important information which are used for identification of abnormal heartbeats. Previously, we have proposed multiple standalone ECG processing schemes such as [28], [29], however, in this work, we intend to propose a lightweight system and benchmark it using multiple databases and classification techniques.…”
Section: Introductionmentioning
confidence: 99%